2014
DOI: 10.4310/ajm.2014.v18.n2.a8
|View full text |Cite
|
Sign up to set email alerts
|

The Euclid-Fourier-Mukai algorithm for elliptic surfaces

Abstract: We describe the birational correspondences, induced by the Fourier-Mukai functor, between moduli spaces of semistable sheaves on elliptic surfaces with sections, using the notion of P -stability in the derived category. We give explicit conditions to determine whether these correspondences are isomorphisms. This is indeed not true in general and we describe the cases where the birational maps are Mukai flops. Moreover, this construction provides examples of new compactifications of the moduli spaces of vector … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…A comprehensive review of the subject and a more complete list of results can be be found in [6]. More recently, t-structures and moduli problems of Bridgeland stable objects in the derived category have been studied in [41,36,42,38,59,9,37,15,35] using a similar approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A comprehensive review of the subject and a more complete list of results can be be found in [6]. More recently, t-structures and moduli problems of Bridgeland stable objects in the derived category have been studied in [41,36,42,38,59,9,37,15,35] using a similar approach.…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive review of the subject and a more complete list of results can be be found in [6]. More recently, t-structures and moduli problems of Bridgeland stable objects in the derived category have been studied in [41,36,42,38,59,9,37,15,35] using a similar approach.Of particular importance for the present paper is the relative Fourier-Mukai transform for elliptic fibrations. This was constructed by Bartocci et al [8] and Bridgeland [10,11] for elliptic surfaces and Friedman, Morgan and Witten [18,19] for stable bundles on elliptic threefolds.…”
mentioning
confidence: 99%
“…We turn now to the proof that Ψ v is an isomorphism in codimension 1, which was given for a surface π : X → P 1 with irreducible fibers in [2], [14]. We thus take up the case when the fibration has at least one reducible fiber.…”
Section: Annales De L'institut Fouriermentioning
confidence: 99%
“…This is a fundamental tool for the study of coherent sheaves on elliptic surfaces, and many properties of moduli spaces are proved (cf. [1], [3], [8], [9], [13]). In [14] and [16], we studied the Hodge numbers and the Picard groups of the moduli spaces under the assumption that all fibers are irreducible.…”
Section: Introductionmentioning
confidence: 99%